Gerakan Literasi Sekolah (GLS) di Sekolah Dasar Unggulan Aisyiyah Taman Harapan Curup - Ummul Khair Siti Partimah Fakar (Institut Agama Islam Negeri Curup, 2019)
This research was conducted to determine the policy of school literacy movement in excellent primary school Aisyiyah Taman Harapan Curup. This research with the theory implementation Eward III namely: communication, resources, commitment, and bureaucracy structure and will describe the supporting and inhibiting factors in implementation the policy of school literacy movement. This research is a descriptive qualitative research which was carried out in a excellent primary school Aisyiyah Taman Harapan Curup in April-Juli 2018. The research subject were vice principal, head of library, and the fourth grade homeroom teacher. Technique collecting data is interview, observation, and documentation. The result of this research are as follows: (1) The policy implementation supported by: (a) implementing agencies communicate through meeting of school element such as management, parents, and teacher. (b) The resources that support this activity such as the potential of teacher funds from parent of the students as soon as goverment and sponsor. (c) commitment from implementing agencies. (d) Bureaucracy structure from part of school. (2) supporting factors in the form of the availability of means to socialize policies, book grant from parents, time and funds, teacher have a passion for learning, while the inhibiting factor teacher must be still reminded related to the policy Standard Operational Procedure and the program that still need to be done each other busy of ustadzah and ustadz which usually make the literacy process in the library and making wall magazine whic sudden because of limited human resources too. Parent often ignore incoming message via whatsapp need for program development so that it is not monotonous and students become bored.Keyword: School Literacy Movement, SDUA THC.